Deferasirox pharmacogenetic influence on pharmacokinetic, efficacy and toxicity in a cohort of pediatric patients. (April 2017) - Allegra, Sarah; De Francia, Silvia; Cusato, Jessica; Arduino, Arianna; Massano, Davide; Longo, Filomena; Piga, Antonio; D'Avolio, Antonio
Aim: We aimed to evaluate the influence of genetic polymorphisms involved in deferasirox metabolism and transport on its pharmacokinetics and treatment toxicity, in a cohort of β-thalassaemic children.Patients & methods: Drug plasma concentrations were measured by a HPLC-UV method. Allelic discrimination for UGT1A1, UGT1A3, CYP1A1, CYP1A2, CYP2D6, MRP2 and BCRP1 polymorphisms was performed by real-time PCR.Results : CYP1A1 rs2606345AA influenced Ctrough (p = 0.001) and t1/2 (p = 0.042), CYP1A1 rs4646903TC/CC (p = 0.005) and BCRP1 rs2231142GA/AA (p = 0.005) influenced Tmax and CYP2D6 rs1135840CG/GG influenced Cmax (p = 0.044). UGT1A1 rs887829TT (p = 0.002) and CYP1A2 rs762551CC (p = 0.019) resulted as predictive factor of ferritin levels and CYP1A1 rs2606345CA/AA (p = 0.021) and CYP1A2 rs762551AC/CC (p = 0.027) of liver iron concentration.Conclusion: Our data suggest the usefulness of deferasirox pharmacogenetics in pediatric treatment optimization.